A meshless fragile points method for rule-based definition of myocardial fiber orientation. (November 2022) - Mountris, Konstantinos A.; Pueyo, Esther
Highlights: A rule-based model for cardiac fiber arrangement is developed using the meshless Fragile Points Method. Atrial and ventricular fiber arrangements are determined based on histology observations. Max and mean fiber angle difference are 3 ∘ and 0.03 ∘, respectively. Fragile Points Method leads to similar precision with Finite Element Method without requiring a mesh definition. Abstract: Background and objective: Rule-based methods are commonly used to estimate the arrangement of myocardial fibers by solving the Laplace problem with appropriate Dirichlet boundary conditions. Existing algorithms are using the Finite Element Method (FEM) to solve the Laplace–Dirichlet problem. However, meshless methods are under development for cardiac electrophysiology simulation. The objective of this work is to propose a meshless rule based method for the determination of myocardial fiber arrangement without requiring a mesh discretization as it is required by FEM. Methods: The proposed method employs the Fragile Points Method (FPM) for the solution of the Laplace–Dirichlet problem. FPM uses simple discontinuous trial functions and single-point exact integration for linear trial functions that set it as a promising alternative to the Finite Element Method. We derive the FPM formulation of the Laplace–Dirichlet and we estimate ventricular and atrial fiber arrangements according to rules based on histology findings for four different geometries. The obtained fiber arrangements from FPM are compared with the ones obtained from FEM by calculating the angle between the fiber vector fields of the two methods for three different directions (i.e., longitudinal, sheet, transverse). Results: The fiber arrangements that were generated with FPM were in close agreement with the generated arrangements from FEM for all three directions. The mean angle difference between the FPM and FEM vector fields were lower than 0 . 030 ∘ for the ventricular fiber arrangements and lower than 0 . 036 ∘ for the atrial fiber arrangements. Discussion: The proposed meshless rule-based method was proven to generate myocardial fiber arrangements with very close agreement with FEM while alleviates the requirement for a mesh of the latter. This is of great value for cardiac electrophysiology solvers that are based on meshless methods since they require a well defined myocardial fiber arrangement to simulate accurately the propagation of electrical signals in the heart. Combining a meshless solution for both the determination of the fibers and the electrical signal propagation can allow for solution that do not require the definition of a mesh. To our knowledge, this work is the first one to propose a meshless rule-based method for myocardial fiber arrangement determination.